Adsorption of Remazol Brillant Green 6B (RBG 6B) on chitin: Process optimization using response surface methodology - Tepe, O. (Global Network Environmental Science & Technology, 2018)
In the present study, the adsorption of Remazol Brillant Green 6B (RBG 6B) on chitin which characterized by BET, FTIR, XRD and SEM analysis was studied. Response surface methodology (RSM) was applied to determine interaction between solution pH, initial RBG 6B concentration and chitin dosage being individual variables and to optimize operating conditions. According to results of variance analysis (ANOVA), the second order polynomial model was statistically significant (P<0.0001) and coefficient of determination value (R-2=0.98) was high. It was determined that dye removal efficiency increased when low solution pH and initial RBG 6B dye concentration and high chitin dosage were used. The maximum dye removal efficiency was obtained as 88% at solution pH of 3.0, initial RBG 6B concentration of 75 mg L-1 and chitin dosage of 5.0 g L-1. The isotherms and kinetics studies showed that Freundlich isotherm and pseudo-second-order kinetics model fitted well to the RBG 6B adsorption data.
Keywords: Adsorption; characterization of chitin; optimization; removal; response surface methodology; RBG 6B